Waiting for Asylum. Everyday Life in Refugee Camps and Asylum Seekers’ Homes as Portrayed in German-Language Literature - Głuszko-Boczoń, Estera (Porównania, 2025)
Refugee camps are an inextricable fixture in the journeys of refugees forced for various reasons to leave behind their homes and set out for a new country not always better than the old one. Whatever the reasons for their departure, refugee camps are mandatory stops on their paths. It is there that the new incomers spend weeks or months awaiting their positive or negative asylum decisions. The purpose of this article is to highlight the multidimensional aspects of everyday life at the camps. The camp realities are vividly portrayed in selected works by Abbas Khider, Elfriede Jelinek and Daniel Zipfel. The authors’ chosen theme retains its relevance today and provides new opportunities for reflection.